Industrial relations : (McGraw-Hill/Irvin, 2005)
The new edition of this classic textbook contains the most up-to-date and theoretically-informed analysis of the processes and practices of industrial relations in Australia. The result is a stronger text than ever before. The changing roles of management, unions, governments and arbitration tribunals are accurately described, while the bargaining processes at all levels and their economic and social outcomes are revealed. This text provides students with a current understanding of the modern labour market, labour process and regulatory institutions, locating the latest trends within a sound conceptual framework. This new edition has been substantially reworked and introduces a number of key contributing authors, in particular Dr Peter Waring who has made significant additions to its overall development.